Aplikacija modela gravitacije na države G7 - Lorenčič, Eva (Naše gospodarstvo, 2014)
We apply the gravity model of trade to the G7 countries with the aim of improving our understanding of the determinants of bilateral trade flows between the G7 countries and their trading partners (a sample of 161 countries). The theoretical section of the paper discusses the theoretical underpinnings of the model. The gravity model is grounded in several theories of international trade. In the empirical section, the OLS method is used to test ten econometric models. We expand on the basic gravity model, in which bilateral trade flows are a function of the GDPs of the two trading partners and of the flight distance between their capitals, by including five dummy variables, the remoteness variable, and a variable measuring the absolute difference in GDP per capita. The latter variable is used for testing the Linder hypothesis against the H-O model. The results are consistent with existing empirical studies and theoretical predictions.
Keywords: razvite države; ekonomski razvoj; mednarodna trgovina; izvoz; svetovno gospodarstvo; modeli